Relationship between adult abundance and successive coral recruitment density in the Tioman Island Marine Park, Malaysia - Muhammad Faiz, Mohd Hanapiah; Saad, Shahbudin; Mukai, Yukinori; Ahmad, Zuhairi (Taylor and Francis Group, 2017)
It is important to understand coral recruitment as coral reefs are regionally in decline. The pattern and magnitude of coral recruitment strongly influence conservation options and management efforts. This study revealed a relationship between adult abundance and coral recruitment patterns at four reef sites in the Tioman Island Marine Park, Malaysia. The coral cover percentage was assessed using a video transect method and coral recruitment was estimated using settlement plates deployed at each reef site. Family Acroporidae dominated the coral cover percentage at most reef sites, while recruitment densities were dominated by acroporids and pocilloporids. The present evidence indicates a positive correlation between adults of Acroporidae and acroporid recruits (r = 0.94, p < 0.01) suggesting that reef recovery may be dependent on the local larval pool.